2016
DOI: 10.18632/oncotarget.10157
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic microenvironment promotes the metastatic seeding of tumor cells via activating the fibronectin 1/secreted phosphoprotein 1-integrin signaling

Abstract: The seeding of tumor cells is a critical step in the process of metastasis, but whether and how the microenvironment of target organs affects metastatic seeding remain largely unknown. Based on cell and mouse models, we found that the metastatic seeding and outgrowth of tumor cells were significantly enhanced in fibrotic lungs. The conditioned medium from both fibrotic lungs and the fibrotic lung-derived fibroblasts (CM-FLF) had a strong activity to chemoattract tumor cells and to inhibit the apoptosis of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…CAFs secrete several signaling molecules, including inflammatory cytokines, growth factors and chemokines, to stimulate cancer cells in the TME, and they remodel the extracellular matrix (ECM) by secreting ECM components . Through these properties, CAFs provide suitable conditions for tumor progression by promoting tumor growth, survival, angiogenesis, inflammation, drug resistance, invasion and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…CAFs secrete several signaling molecules, including inflammatory cytokines, growth factors and chemokines, to stimulate cancer cells in the TME, and they remodel the extracellular matrix (ECM) by secreting ECM components . Through these properties, CAFs provide suitable conditions for tumor progression by promoting tumor growth, survival, angiogenesis, inflammation, drug resistance, invasion and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis formation has been ascribed to both tumor intrinsic and microenvironmental effects of the LPA pathway [ 49 ]. At the intersection of these two phenotypes, fibrosis has been reported as a “soil” for the seeding of metastases [ 50 , 51 ], expansion of micrometastases [ 16 ], promotion of tumor viability [ 10 ], and immune effects [ 17 ], suggesting the hypothesis that LPA-induced fibrosis may be a mechanism of metastasis promotion. This hypothesis was contrary to published data where breast cancer cells with a LPA1 knockdown were metastasis suppressed [ 18 ], suggesting a tumor cell-intrinsic effect, but did not preclude an indirect microenvironmental effect or a transdifferentiation of carcinoma cells to myoepithelial cells [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The levels of FN1 do not seem to differ significantly between patients with and without HBV integration into FN1 (Ding et al ., ; Sung et al ., ), suggesting that some integration events may not have a direct impact on HCC development (Sung et al ., ) and these genomic sites are perhaps more prone to HBV integration but do not appear to contribute to HCC. Nonetheless, a report showed that activation of FN1 creates a microenvironment to promote the metastatic seeding of tumour cells in lung cancer (Zhang et al ., ). Hence, it is also possible that while FN1 may not have a direct effect on the development of the tumour itself, it may create a microenvironment in adjacent non‐tumour tissues to facilitate tumour metastasis.…”
Section: Fusion Sites Within Hbv and The Human Genomementioning
confidence: 99%